Comparing forward and backward chaining in teaching Olympic weightlifting. Issue 1 (24th October 2018) - Moore, James W.; Quintero, Laura M.
Abstract : The popularity of Olympic‐style weightlifting in fitness routines is growing, but participating in these exercises with improper technique places lifters at increased risk for injury. Fitness training professionals have developed multiple teaching strategies, but have not subjected these strategies to systematic evaluation, particularly with novice lifters. Two strategies recommended by professional training organizations are akin to forward and backward chaining, which have been shown effective at teaching other novel, complex behaviors. The present study compared these forward‐ and backward‐chaining‐like strategies to teach novice lifters "the clean" and "the snatch, " two Olympic weightlifting movements frequently incorporated into high‐intensity training programs. Participants performed lifts taught with forward chaining more accurately than lifts taught with backward chaining.